The Effect of Intellectual Capital, Company Growth, and Board Diversity on Company Value - Leny Suzan; Meldiyana Trianadifa Suharto (UNIVERSITAS PAKUAN, 2023)
This Company Value is an investor's perception of the success of a company that is often correlated with stock price. A high stock price is considered to have a high company value and will have an impact on the company's success in the future. The research was conducted with the aim of determining the influence of intellectual capital, company growth, and board diversity on company value are state-owned companies listed on IDXBUMN20 in 2018-2021. The sampling technique carried out was purposive sampling and obtained a sample number of 60 samples consisting of 15 companies with a research period of 4 years. There are 8 outlier data, so the observation data in this study is 52 samples. The analysis method used in this study is regression analysis of panel data processed using Eviews 12 software. The results of the research conducted prove that intellactual capital, company growth, and board diversity simultaneously affect company value. Partially, intellectual capital variables have a positive and significant effect on company value, company growth variables have no effect on company value, board diversity variables have no effect on company value.